What caused the euro area post-pandemic inflation? An application of Bernanke and Blanchard (2023) - Óscar Arce; Matteo Ciccarelli; Antoine Kornprobst; Carlos Montes-Galdón (European Central Bank (ECB), 2024)
This paper applies the semi-structural model proposed by Bernanke and Blanchard (2023) to analyse wage growth, price inflation and inflation expectations in the euro area. It is part of a broader project coordinated by Bernanke and Blanchard to provide a unified framework for analysing and comparing global inflation dynamics across the major world economic areas, including US, euro area, Canada, UK, and Japan. The paper makes four main contributions. First, it estimates the model using quarterly data from the euro area covering the period from the first quarter of 1999 to the second quarter of 2023. Second, it conducts an empirical assessment of how euro area price inflation responds to various exogenous shocks. This includes evaluating how shock transmission evolved during the pandemic and comparing it with experience in the United States. Third, the model decomposes the drivers of wage growth and price inflation in the post-pandemic period. It emphasises the transmission channels and the respective roles of supply and demand forces that have contributed to the recent inflationary surge. Notably, it identifies the impact of labour market tightness, productivity, global supply chain disruptions and energy and food price shocks. Finally, the model generates conditional projections based on these exogenous shocks, enabling a more robust cross-check of inflation forecasts during times of significant global economic disturbances.
Keywords: C5; E47; E52; E58; F4; 330; econometric modelling; forecasting and simulation; monetary policy; central banking